2009
DOI: 10.2340/16501977-0417
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Qigong in patients with burnout: A randomized controlled trial

Abstract: In this study, a Qigong intervention twice a week for 12 weeks had no additional effect beyond basic care for patients with burnout.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 32 publications
0
41
0
2
Order By: Relevance
“…These studies were conducted in Hong Kong [2830, 3537], Sweden [34], and Mainland China [31–33, 38, 39], respectively. Ten of them were published in peer-review journals with full texts and the remaining two were unpublished master theses [33, 39].…”
Section: Resultsmentioning
confidence: 99%
“…These studies were conducted in Hong Kong [2830, 3537], Sweden [34], and Mainland China [31–33, 38, 39], respectively. Ten of them were published in peer-review journals with full texts and the remaining two were unpublished master theses [33, 39].…”
Section: Resultsmentioning
confidence: 99%
“…Two studies showed that Qigong was as effective as physical exercise [27, 28]. Three studies did not find a significant difference between the Qigong intervention and the control group [29–31]. …”
Section: Resultsmentioning
confidence: 99%
“…Of the ten studies, five conducted intention-to-treat (ITT) statistical analyses, two conducted completers analyses [25, 29], and one performed both ITT and completer analyses [31]. Two studies did not report the details of their data analysis methods [13, 23].…”
Section: Resultsmentioning
confidence: 99%
“…Affirmative responses were followed-up by the physician in a structured interview form conforming to the criteria of the Diagnostic and Statistical Manual of Mental Disorders, Fourth Revision, for the diagnostic assessment of mood and anxiety disorders (DSM-IV) [23]. These criteria have been previously described in several studies and are highly related to clinical burnout [22,24,25]. …”
Section: Methodsmentioning
confidence: 99%